PENGARUH PEMBERIAN KADAR AIR BERBEDA TERHADAP PERTUMBUHAN DAN PRODUKSI HIJAUAN TANAMAN Indigofera zollingeriana - M. A. D., Ranti; Suryani, N. N; Budiasa, I K. M. (Jurnal Peternakan Tropika, 2017)
This study aimed to determine the water content suitable for plant growth and forage plant Indigofera zollingerianaproduction. The research was carried out for 15 weeks in Greenhouse Research Station Faculty of Animal Husbandry at Udayana University, Jalan Raya Sesetan, GangMarkisa Denpasar. The experimental design used was completely randomized design (CRD) with five treatments, they were: 100%, 90%, 80%, 70%, and 60% of field capacity with five replications. The results showed that the plant height and number of leaves were significant (P <0.05) at the highest at water provision content 100% of field capacity, respectively 58.80 and 13.80 cm pieces. Similarly, leaf weight, stem weight, root weight and total weight of forage were significant (P <0.05), the highest in the provision of water content of 100% compared to other treatments, respectively: 10.58%; 6.82%: 8.04% and 17.40%. Dry weight ratio of leaves with stems in the provision of water content of 100%, 90% and 80% had no significant differences (P <0.05) in the provision of water content of 70%, i.e. 7.74% was significantly lower (P <0.05 ) compared to treatment A1. Total forage dry weight ratio with roots also had the lowest significance (P <0.05) in treatment A4 compared with A1 i.e. equal to 10.13%. In the provision of water content of 60%, it did not cause their growth and production
Keywords: Indigofera zollingeriana, water content, growth, production